2022
DOI: 10.1021/acsami.2c11359
|View full text |Cite
|
Sign up to set email alerts
|

Gate-Modulated High-Response Field-Effect Transistor-Type Gas Sensor Based on the MoS2/Metal–Organic Framework Heterostructure

Abstract: The high surface-to-volume ratio and decent material properties of two-dimensional (2D) transition metal dichalcogenides (TMDs) make them advantageous as an active channel in field-effect transistor (FET)-type gas sensing devices. However, most existing TMD gas sensors are based on a two-terminal resistance-type structure and suffer from low responsivity and slow response, which has urged materials optimization as well as device engineering. Metal–organic frameworks (MOFs) have a large number of ordered bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…155 This drawback requires a good solution before they can be put into practice in a variety of sensing situations. Recently, Zhu et al 156 reported the fabrication of FET sensors based on MoS 2 /MOF heterojunctions to detect NH 3 (Figure 7d). The electrical properties of FDM-23 can be improved by modifying the structure of MoS 2 .…”
Section: Gas Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…155 This drawback requires a good solution before they can be put into practice in a variety of sensing situations. Recently, Zhu et al 156 reported the fabrication of FET sensors based on MoS 2 /MOF heterojunctions to detect NH 3 (Figure 7d). The electrical properties of FDM-23 can be improved by modifying the structure of MoS 2 .…”
Section: Gas Sensingmentioning
confidence: 99%
“…(d) Schematic diagram of the MoS 2 /MOF FET device. Reproduced with permission 156. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional (2D) Cu 6 (C 8 H 4 O 4 ) 6 (H 2 O) 6 $H 3 [P(W 3 O 10 ) 4 ] (FDM-23) MOF with ultrathin thickness and 2D morphology, was a Cu-based MOF exfoliated from 3D MOF, exhibiting notable electrocatalysis, sensing and separation performance. [29][30][31][32] It is expected that the released copper ions of 2D FDM-23 MOF can trigger GSH elimination, then catalyze Fenton-like reaction, signicantly increasing the CDT effect.…”
Section: Introductionmentioning
confidence: 99%
“…The substantial innovation of this work is to provide a universal platform that is based on a high-performance carbon nanotube FET onto which any type of MOF can be grown. There have been a few recent reports where MOFs have been grown on nanowire FETs, organic FETs, MoS 2 -FET, [13][14][15] and on graphene-FETs. [2] But up to now, no work has been reported where MOFs have been grown on CNTFETs.…”
mentioning
confidence: 99%